Evaluation of SDC's vocational skills development activities - Maurer, Markus [Verfasser]; Arnold, Rolf [Verfasser]; Gonon, Philipp [Verfasser]; Michaelowa, Katharina [Verfasser]; Wieckenberg, Uwe [Verfasser] (My University, 2011)
The report presents the findings of an external evaluation of the Swiss Agency for Development and Cooperation's (SDC) Vocational Skills Development (VSD) activities. "The evaluation portfolio covered 10 projects and programmes in 9 countries (Albania, Bangladesh, Burkina Faso, Ecuador, Mali, Moldova, Nepal, Nicaragua, Peru). The report is structured along the lines of the OECD DAC Evaluation Criteria. Overall, SDC's VSD activities can be rated as 'satisfactory'. The main strength of the programmes under review is their strong orientation towards the needs of their respective national and local contexts, with an awareness of labour market realities. Strong labour market-orientation is also the basis for the contribution to higher employment by SDC's VSD activities, as well as for their achievements in the domain of more fundamental changes to VSD systems. The main weakness of activities under review is that target populations are not always being reached, particularly when it comes to socioeconomically disadvantaged people and females." (Text excerpt, BIBB-Doku)
Keywords: I 1.1 Systemberatung; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; Berufsbildung; Projekt; Internationale Zusammenarbeit; Entwicklungshilfe; Evaluation; Schweiz